Pengaruh Pencucian Sperma dengan Lama Waktu Sentrifugasi yang Berbeda Terhadap Kualitas Sperma Kambing Bligon (Effect of Sperm Washing with Different Centrifugation Duration on Sperm Quality of Bligon Buck) - Sigit Bintara (Buletin Peternakan, 2010)
The objective of the experiment was to examine the effect of sperm washing using SpermRinse with different centrifugation duration (15, 20, and 25 minutes) on the quality of Bligon spermatozoa. Sperm was collected usingartificial vagina from six bucks of 2 (two) year olds. Data were collected for motility, viability, and abnormality of the spermatozoa. Characteristics of the fresh sperm were analyzed based on mean and deviation standard, and followed by Duncan’s New Multiple Range Test (DMRT). The results showed that washing Bligon buck sperm using SpermRinse with different centrifugation times had very significant effect (P≤0.01) on the motility, viability, and abnormality ofspermatozoa. It is concluded that washing Bligon buck sperm using SpermRinse with centrifugation at 1.500 rpm (r = 5.5 cm) could increased sperm quality, of which 20 minutes was the best centrifugation time.(Key word: Bligon Buck, Sperm, SpermRinse, Sperm quality)